EVALUASI KEBIJAKAN PENGEMBANGAN PUBLIKASI BEREPUTASI INTERNASIONAL BIDANG SOSIAL HUMANIORA DI ITS SURABAYA - Choirul Mahfud; Dyah Satya Yoga Agustin (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
This article discuses on policy evaluation research of publication at ITS campus. More specifically, concerning international publications in the aspect of Social Humanities. It is because universities are now required to pay attention to multidisciplinary studies that enable research institutions to seize opportunities and overcome challenges influenced by many factors, aspects, and approaches. Therefore, understanding and conducting a more comprehensive policy evaluation is always essential to do. In this case, policy evaluation is seen as a simple way of evaluation. From the achievements of research and international publications that have been carried out or have been produced. What are the supporting and inhibiting factors of internationally reputable publication activities carried out on the ITS Surabaya campus? The study results show that ITS lecturers' achievements and contributions in international publications in the social and humanities field should be appreciated and supported by systematic, comprehensive, and sustainable policies. The reason is, seeing the number of lecturers in the social and humanities field is also not small, although not too many. Therefore, solutions for making research-based policies in the social and humanities field need to be improved. It is the key to supporting the publication step. Without a research policy, the publication will be challenging to do in an organized and sustainable manner. Obstacles exist from internal and external that can be understood by relevant stakeholders to take alternative steps to solve them through collaboration and synergy in publications.